Intratumorally injected pro-inflammatory allogeneic dendritic cells as immune enhancers: a first-in-human study in unfavourable risk patients with metastatic renal cell carcinoma. Issue 1 (20th June 2017) - Laurell, Anna; Lönnemark, Maria; Brekkan, Einar; Magnusson, Anders; Tolf, Anna; Wallgren, Anna Carin; Andersson, Bengt; Adamson, Lars; Kiessling, Rolf; Karlsson-Parra, Alex
Abstract : Background: Accumulating pre-clinical data indicate that the efficient induction of antigen-specific cytotoxic CD8+ T cells characterizing viral infections is caused by cross-priming where initially infected DCs produce an unique set of inflammatory factors that recruit and activate non-infected bystander DCs. Our DC-based immunotherapy concept is guided by such bystander view and accordingly, we have developed a cellular adjuvant consisting of pre-activated allogeneic DCs producing high levels of DC-recruiting and DC-activating factors. This concept doesn't require MHC-compatibility between injected cells and the patient and therefore introduces the possibility of using pre-produced and freeze-stored DCs from healthy blood donors as an off- the-shelf immune enhancer. The use of MHC-incompatible allogeneic DCs will further induce a local rejection process at the injection site that is expected to further enhance recruitment and maturation of endogenous bystander DCs. Methods: Twelve intermediate and poor risk patients with newly diagnosed metastatic renal cell carcinoma (mRCC) where included in a phase I/II study. Pro-inflammatory allogeneic DCs were produced from a leukapheresis product collected from one healthy blood donor and subsequently deep-frozen. A dose of 5–20 × 10 6 DCs (INTUVAX) was injected into the renal tumor twice with 2 weeks interval before planned nephrectomy and subsequent standard of care. Results: No INTUVAX-related severe adverse events were observed. A massive infiltration of CD8+ T cells was found in 5 out of 12 removed kidney tumors. No objective tumor response was observed and 6 out of 11 evaluable patients have subsequently received additional treatment with standard tyrosine kinase inhibitors (TKI). Three of these 6 patients experienced an objective tumor response including one sunitinib-treated patient who responded with a complete and durable regression of 4 brain metastases. Median overall survival (mOS) is still not reached (currently 42.5 months) but has already passed historical mOS in patients with unfavourable risk mRCC on standard TKI therapy. Conclusions: Our findings indicate that intratumoral administration of proinflammatory allogeneic DCs induces an anti-tumor immune response that may prolong survival in unfavourable risk mRCC-patients given subsequent standard of care. A randomized, multi-center, phase II mRCC trial (MERECA) with INTUVAX in conjuction with sunitinib has been initiated. Trial registration: Clinicaltrials.gov identifier: NCT01525017 .